2018
DOI: 10.3390/cryst8060249
|View full text |Cite
|
Sign up to set email alerts
|

Sonocrystallization—Case Studies of Salicylamide Particle Size Reduction and Isoniazid Derivative Synthesis and Crystallization

Abstract: Two case studies of salicylamide particle size reduction and isoniazid derivative synthesis and crystallization realized using sonocrystallization were investigated. The size, habit, structure, thermal behavior, and spectrometric properties of sonocrystallized crystals were analyzed through scanning electron microscopy (SEM), powder X-ray diffractometry (PXRD), differential scanning calorimetry (DSC), and Fourier transform infrared (FTIR) spectroscopy. The effects of the operating parameters, such as sonicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
(35 reference statements)
0
4
0
Order By: Relevance
“…It can reduce the metastable zone width, and generate rapid, uniform mixing, which reduces the agglomeration of particles [18,19]. Higher sonication intensity and longer sonication time favour the formation of smaller crystals with narrow PSD [20][21][22].Impinging jet crystallization is a relatively new field for the researchers in pharmaceutical manufacturing and industrial crystallization [23]. However, it is proved that this method effectively reduces particle size, as well as it has the potential advantage to produce reproducible products with small average particle size and narrow PSD [24].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It can reduce the metastable zone width, and generate rapid, uniform mixing, which reduces the agglomeration of particles [18,19]. Higher sonication intensity and longer sonication time favour the formation of smaller crystals with narrow PSD [20][21][22].Impinging jet crystallization is a relatively new field for the researchers in pharmaceutical manufacturing and industrial crystallization [23]. However, it is proved that this method effectively reduces particle size, as well as it has the potential advantage to produce reproducible products with small average particle size and narrow PSD [24].…”
mentioning
confidence: 99%
“…It can reduce the metastable zone width, and generate rapid, uniform mixing, which reduces the agglomeration of particles [18,19]. Higher sonication intensity and longer sonication time favour the formation of smaller crystals with narrow PSD [20][21][22].…”
mentioning
confidence: 99%
“…Similar trend was also observed in our previous case study for sonocrystallization of salicylamide. [ 26 ]…”
Section: Resultsmentioning
confidence: 99%
“…[ 16‐18 ] With the emerging of sonocrystallization in practical use, several case studies have been reported in the literature in recent years for recrystallization of biological compounds such as aspirin, l ‐arginine hydrochloride, ferulic acid, cinnamic acid, oxalic acid, l ‐phenylalanine, salicylamide, isoniazid derivative, telmisartan, lactose, lysozyme, and l ‐glutamic acid. [ 19‐30 ]…”
Section: Introductionmentioning
confidence: 99%